Design and Production of a Paper Shredding Machine - W.A. Akpan; I.I. Nyaudo; E.S. Umana; W.I. Dawson; S.I. Bassey (Engineering And Technology Journal, 2024)
There are countless cases of cooperate and government espionage, identity theft, sensitive information leaks. This all led to the need for government agencies, private and public institutions and even private individuals to protect their sensitive information and prevent it from falling into the wrong hands. The act of discarding whole, readable documents containing sensitive information poses huge risks to an individual or organization, as these documents can be retrieved from a trash bin and the information they contain easily accessed. This has led to a number of identity theft cases, where a crime is committed using the information of an unsuspecting individual. Although advancements in information technology have resulted in electronic transmission and storage of information, a good number is still communicated via paper. This newly designed paper shredding machine utilized chain and sprocket in the power transmission which offers a high transmission efficiency unlike some paper shredding machines that used belt and pulley which cause slip and transmission losses. The machine architecture is very compact with ergonomically suitable features, and the performance is high. The shredding efficiency was 94%.Improvement on further work to improve the shredding efficiency is required.